Pore water pressure of sandy soil improved with steel slag under the influence seismic load - Ahmed, Hassan Ali; Abbas, Jawdat K. (Edelweiss Applied Science and Technology, 2024)
In this study, we examined the change in pore water pressure and the liquefaction phenomenon on sandy soils improved using steel slag, which is one of the industrial wastes of iron and steel factories, with a mixing ratio of (3,6,9,12,15) % using a shaking table under the influence of the Halabja earthquake, which is active in the seismic zone located in northeastern Iraq, the foundation that was used in the examination is a circular foundation with dimensions of (100) mm diameter. Pore water pressure sensors, number A, were placed inside the soil, where the first was at a distance of 5cm from the bottom of the foundation and the second was at a distance of 25cm from the bottom of the foundation. Based on the previous findings, the pore water pressure is higher at a depth of 5 cm than at 25 cm, adding steel slag to the sandy soil led to a reduction in the pore water pressure over the two distances that were measured from the bottom of the foundation, where the higher the percentage of steel slag after 6, the lower the value of the pore water pressure, When steel slag is added at depths of 5 and 25 cm, the Halabjah earthquake exhibits non-linear, overlapping behavior that intensifies as steel slag is added.